Maternal, Fetal, and Child Outcomes of Mental Health Treatments in Women: A Meta‐Analysis of Pharmacotherapy. Issue 3 (4th May 2021) - Viswanathan, Meera; Middleton, Jennifer Cook; Stuebe, Alison M.; Berkman, Nancy D.; Goulding, Alison N.; McLaurin‐Jiang, Skyler; Dotson, Andrea B.; Coker‐Schwimmer, Manny; Baker, Claire; Voisin, Christiane E.; Bann, Carla; Gaynes, Bradley N.
Abstract : Objective: The authors systematically reviewed evidence on pharmacotherapy for perinatal mental health disorders. Methods: The authors searched for studies of pregnant, postpartum, or reproductive‐age women with mental health disorders treated with pharmacotherapy in MEDLINE, EMBASE, PsycINFO, the Cochrane Library, and trial registries from database inception through June 5, 2020 and surveilled literature through March 2, 2021. Outcomes included symptoms; functional capacity; quality of life; suicidal events; death; and maternal, fetal, infant, or child adverse events. Results: 164 studies were included. Regarding benefits, brexanolone for third‐trimester or postpartum depression onset may be associated with improved depressive symptoms at 30 days when compared with placebo. Sertraline for postpartum depression may be associated with improved response, remission, and depressive symptoms when compared with placebo. Discontinuing mood stabilizers during pregnancy may be associated with increased recurrence of mood episodes for bipolar disorder. Regarding adverse events, most studies were observational and unable to fully account for confounding. Evidence on congenital and cardiac anomalies for treatment compared with no treatment was inconclusive. Brexanolone for depression onset in the third trimester or the postpartum period may be associated with risk of sedation or somnolence, leading to dose interruption or reduction when compared with placebo. Conclusions: Evidence from few studies supports the use of pharmacotherapy for perinatal mental health disorders. Although many studies report on adverse events, they could not rule out underlying disease severity as the cause of the association between exposures and adverse events. Patients and clinicians need to make informed, collaborative decisions on treatment choices. Highlights: Few studies have been conducted in pregnant and postpartum women on the benefits of pharmacotherapy; many studies report on harms but are of low quality Brexanolone probably improves depressive symptoms; it may increase the risk of sedation or somnolence, leading to dose interruption or reduction. Sertraline may improve response, remission, and depression and anxiety symptoms. Mood stabilizers may reduce recurrence and increase time to recurrence Although associations may exist between psychotropic medications and adverse events, causality cannot be inferred. The paucity of evidence does not mean that pharmacotherapy is not beneficial, nor that harms do not exist; rather, it underscores the absence of high‐quality research